2022
DOI: 10.2478/sjecr-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of “Sneznik-1/79” Mineral Water on Anthropometric, Functional and Biochemical Parameters of Professional Basketball Players: Role of Oxidative Stress

Abstract: Adequate hydration represents the balance between the water intake and loss and has an unambiguous significance for public health and it is essential to sustain life. The changes in electrolyte balance which occur during and after training affect on athletes health and performance. Therefore, fluid replacement with adequate mineral composition is of utmost importance. The aim of the present study was to examine the influence of low mineral water from the well Sneznik-1/79 on anthropometric, functional, biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Moreover, one research shows that even when rich mineral water was applied, these ions could not affect the secretion of adiponectin from adipocytes and thus do not change the metabolic activity of adipose tissue [ 26 ]. Our results are in line with the results of the previous studies, which indicated no significant variations in basic anthropometric characteristics such as body mass and body mass index after consumption of low mineral water [ [26] , [27] , [28] ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, one research shows that even when rich mineral water was applied, these ions could not affect the secretion of adiponectin from adipocytes and thus do not change the metabolic activity of adipose tissue [ 26 ]. Our results are in line with the results of the previous studies, which indicated no significant variations in basic anthropometric characteristics such as body mass and body mass index after consumption of low mineral water [ [26] , [27] , [28] ].…”
Section: Discussionsupporting
confidence: 93%